Estimates of ozone concentrations and attributable mortality in urban, peri-urban and rural areas worldwide in 2019 - Daniel A Malashock; Marissa N DeLang; Jacob S Becker; Marc L Serre; J Jason West; Kai-Lan Chang; Owen R Cooper; Susan C Anenberg (Environmental Research Letters, 2022)
City-level estimates of ambient ozone concentrations and associated disease burdens are sparsely available, especially for low and middle-income countries. Recently available high-resolution gridded global ozone concentration estimates allow for estimating ozone concentrations and mortality at urban scales and for urban-rural catchment areas worldwide. We applied existing fine resolution global surface ozone estimates, developed by integrating observations (8834 sites globally) with nine atmospheric chemistry models, in an epidemiologically-derived health impact function to estimate chronic respiratory disease mortality worldwide in 2019. We compared ozone season daily maximum 8 h mixing ratio concentrations and ozone-attributable mortality for urban areas worldwide (including cities and densely-populated towns), and their surrounding peri-urban, peri-rural, and rural areas. In 2019, population-weighted mean ozone among all urban-rural catchment areas was greatest in peri-urban areas (52 ppb), followed by urban areas (cities and towns; 49 ppb). Of 423 100 estimated global ozone-attributable deaths, 37% (147 100) occurred in urban areas, where 40% of the world’s population resides, and 56% (254 000) occurred in peri-urban areas (<1 h from an urban area), where 47% of the world’s population resides. Across 12 946 cities (excluding towns), average population-weighted mean ozone was 51 ppb (sd = 13 ppb, range = 10–78 ppb). Three quarters of the ozone-attributable deaths worldwide (77%; 112 700) occurred in cities of South and East Asia. City-level ozone-attributable mortality rates varied by a factor of 10 across world regions. Ozone levels and attributable mortality were greatest in Asian and African cities; however, cities of higher-income regions, like high-income Asia Pacific and North America, continue to experience high ozone concentrations and attributable mortality rates, despite successful national air quality measures for reducing ozone precursor emissions. The disproportionate magnitude of ozone mortality compared with population size in peri-urban areas indicates that reducing ozone precursor emissions in places that influence peri-urban concentrations can yield substantial health benefits in these areas.